UNDERSTOREY FLORA OF SOUTHWESTERN BUNGO RANGE - Meekiong, Kalu; Mohd Effendi, Wasli; Hafsah, Nahrawi; Zinnirah, Shabdin (UNIMAS Publisher, 2023)
Bungo Range National Park is located in Kuching division, shared by two small districts, Bau and Padawan. It is about 67 km journey by road from Kuching City and, about 23 km away from the small town of Bau. The park is gazetted in the year 2009 (Swk, L.N.10) as the 22nd national park under the National Park and Nature Reserve Ordinance, 1990 of Sarawak. The park is the largest national park in Kuching division with the coverage area of 8,096 ha. The landscape of Bungo Range National Park consists of hilly terrain with elevation ranging from 300 to 950 meters above sea level. Among the unique physical features of Bungo Range National Park is the crescent-like shaped of the range. Furthermore, the upper part of the range consisted of sandstone which is bedded on the limestone rock. Perhaps, these unique geological features of Bungo Range promote diverse richness in microhabitats.